Circular RNAs: Emerging Role in Cancer Diagnostics and Therapeutics - Rajappa, Anuva; Banerjee, Sucharita; Sharma, Vivek; Khandelia, Piyush (Frontiers in Molecular Biosciences, 2020)
Circular RNAs (circRNAs) are rapidly coming to the fore as major regulators of gene expression and cellular functions. They elicit their influence via a plethora of diverse molecular mechanisms. It is not surprising that aberrant circRNA expression is common in cancers and they have been implicated in multiple aspects of cancer pathophysiology such as apoptosis, invasion, migration, and proliferation. We summarize the emerging role of circRNAs as biomarkers and therapeutic targets in cancer.